Bovine innate immune phenotyping via a standardized whole blood stimulation assay - Cian Reid (Nature Portfolio, 2021)
Abstract Cattle vary in their susceptibility to infection and immunopathology, but our ability to measure and longitudinally profile immune response variation is limited by the lack of standardized immune phenotyping assays for high-throughput analysis. Here we report longitudinal innate immune response profiles in cattle using a low-blood volume, whole blood stimulation system—the ImmunoChek (IChek) assay. By minimizing cell manipulation, our standardized system minimizes the potential for artefactual results and enables repeatable temporal comparative analysis in cattle. IChek successfully captured biological variation in innate cytokine (IL-1β and IL-6) and chemokine (IL-8) responses to 24-hr stimulation with either Gram-negative (LPS), Gram-positive (PamCSK4) bacterial or viral (R848) pathogen-associated molecular patterns (PAMPs) across a 4-month time window. Significant and repeatable patterns of inter-individual variation in cytokine and chemokine responses, as well as consistent high innate immune responder individuals were identified at both baseline and induced levels. Correlation coefficients between immune response read-outs (IL-1β, IL-6 and IL-8) varied according to PAMP. Strong significant positive correlations were observed between circulating monocytes and IL-6 levels for null and induced responses (0.49–0.61) and between neutrophils and cytokine responses to R848 (0.38–0.47). The standardized assay facilitates high-throughput bovine innate immune response profiling to identify phenotypes associated with disease susceptibility and responses to vaccination.